Exemption of Agricultural Income From Taxati on Under Income Tax Act- How Far Justi fied? - Bhardwaj , Eshaan (Trinity Law Review, 2024)
The definition of agricultural income is very broad as it  includes not only agricultural produce but also various  other things defined under Section 2(1A) of the Income  Tax Act, 1961. This section defines agricultural income as  follows: - Rent or income from agricultural land in India  Any rent or income from agricultural land is agri cultural income. Rent or income earned is treated as  agricultural income only if land is the direct and actual  source and not a secondary or indirect source. • Any income derived from any agricultural activity in  the country including processing of agricultural pro duce to make it marketable and sale of such products.  Income earned is treated as agricultural if a process is  carried out to manufacture a product, which is mar ketable and this process has not changed its original  nature.
Keywords: property tax; circumstances; applicable